Proceedings of First International Conference on Information and Communication Technology for Intelligent Systems: Volume 1 - Satapathy, Suresh Chandra; Das, Swagatam (Smart Innovation, Systems and Technologies, 2016)
This volume contains 59 papers presented at ICTIS 2015: International Conference on Information and Communication Technology for Intelligent Systems. The conference was held during 28th and 29th November, 2015, Ahmedabad, India and organized communally by Venus International College of Technology, Association of Computer Machinery, Ahmedabad Chapter and Supported by Computer Society of India Division IV - Communication and Division V - Education and Research. This volume contains papers mainly focused on ICT for Computation, Algorithms and Data Analytics etc.